Indigenous traditional knowledge of riparian medicinal flora utilized by ethnic communities along the Beas River in Himachal Pradesh, India - Thakur, Neha; Nitesh Kumar; Kumar, Sanjeev; Sharma, Dushyant (Ethnobotany Research and Applications, 2024)
Background: The indigenous flora plays a crucial role in both the cultural heritage and customs of Himalayan local societies, while also playing a significant role in supporting their livelihoods. Local communities in the region rely extensively on a diverse range of wild berries, food, therapeutic plants, and more to fulfill their daily needs. The primary means of sustenance for these tribal communities heavily relies on natural resources, leading to their extensive traditional knowledge. Methods: The ethnomedicinal data was gathered using field surveys, open discussions, and semi-structured questionnaires by ethnic communities. Interviews were conducted with 217 local respondents, comprising 92 women and 125 men. Quantitative ethnobotanical tools, including use value, and informant consensus factor, were applied to analyze the generated data. Results: In the ethnobotanical study, 67 floras spanning 47 families were reported from interviews with local informants, which revealed the usage of therapeutic plants to treat 73 diseases across 11 ailment categories. The highest ICF value (1) is observed in excretory disorders, followed by circulatory disorders (0.94). In our study, Murraya koenigii (0.79) and Mallotus philippensis (0.77) showed the highest value of use value. Conclusion: This research illustrates that the variety of indigenous plants utilized by the residents of Himachal Pradesh is evident not just in the number of species but also in the manifold purposes they serve. Consequently, there is a crucial requirement to document this indigenous information and conduct thorough phytochemical explorations to assess potentially active compounds in herbs, providing evidence of their efficacy. Keywords: Asteraceae, economic value, quantitative tools, excretory disorders